Paper-based sol-gel thin films immobilized cytochrome P450 for enzyme activity measurement - Nuchtavorn, Nantana; Leanpolchareanchai, Jiraporn; Suntornsuk, Leena; Macka, Mirek (Analytica chimica acta, 2020)
Cytochrome P450 (CYP450), and in particular CYP3A4, is the most abundantly expressed CYP450 isozyme implicated in many drug-drug and medicinal plant-drug interactions. Therefore, incorporation of CYP3A4 enzyme screening at an early stage of drug discovery is preferable in order to avoid enzymatic interactions. Here we present for the first time a paper-based CYP3A4 immobilized sol-gel-derived a platform using resorufin benzyl ether as a fluorogenic enzyme substrate used to investigate enzyme activity. The fluorescence intensity of the product can be simply quantified by using a handheld digital microscope and an image analysis software. The limit of quantitation was 0.35 μM with good precision (RSDs < 4.1%). Furthermore, the assay of CYP3A4 activity on the developed paper-based device provided comparable results with those obtained from conventional well-plates (p > 0.05), while offering simplicity and lower cost. Kinetic parameters of the immobilized CYP3A4 in sol-gel coated paper were calculated from the Lineweaver-Burk plot, including Michaelis constant (Km) and maximum velocity (Vmax), which were 2.71 ± 0.35 μM and 0.43 ± 0.05 μM/min, respectively. Moreover, a functional test of these devices was conducted by assessments of known CYP3A4 inhibitors (i.e. ketoconazole, itraconazole) and inducers (i.e. phenytoin, carbamazepine). To further demonstrate the broad range of uses, the devices were utilized to assay plant extracts i.e. Areca catechu seeds, Camellia sinensis leaves, Eclipta prostrata aerial part, providing results in good agreement with previous studies. Furthermore, the sol-gel immobilized enzyme stored at 4 °C can increase storage stability, offering the activity of 86.3 ± 0.4% after 3-weeks storage, equivalent to the activity of the free enzyme solution after 1-week storage. The developed paper-based devices offer versatility, portability and low-cost.
Keywords: ethery; aktivace enzymů; Gels; Sol-gel; Enzyme Activation; Cytochrome P450 enzyme; Oxazines; Molecular Structure; lidé; Fluorescence microscope; Paper; molekulární struktura; Enzymes, Immobilized; gely; systém (enzymů) cytochromů P-450; benzenové deriváty; oxaziny; Ethers; Benzene Derivatives; enzymy imobilizované; Paper-based devices; Cytochrome P-450 Enzyme System; papír; Humans